Pendistribusian Zakat kepada Bukan Mustahik - Farida Arianti; Isra Mardani; Zulfahmi; Nabila Zakiyah; Debby Triana Dewi; M. Ihsanul Fikri (Journal of Islamic Law and Wisdom, 2025)
The life of the people of Nagari X submits zakat to create silaturrahmi to all local people in the surau. Malin distributes zakat equally to all those in the muzakki's house. The purpose of this study explains the purpose of zakat to increase silaturrahmi with relatives and neighbors in the vicinity who understand the text of the QS. Al-Taubah verse 60. As well as explaining the understanding of people who have the right to receive zakat. The research method is descriptive qualitative with a phenomenological approach in Nagari X. The data collection technique is by in-depth interviews with the community and local religious leaders. The analysis was carried out descriptively qualitatively. The research findings state that Malin submitted zakat to people who attended the zakat handover meeting. Zakat is divided based on the number of people present at the meeting. The nominal zakat is only for shopping for light things under Rp. 50,000. in field data. The conclusion of this study shows that the distribution of zakat is based on the moment of the social gathering event between the community to strengthen brotherhood, but this does not have an impact on the purpose of zakat in Islamic law, which is to make zakat recipients prosperous and improve their economy. Therefore, the method of zakat distribution in Nagari X is not in accordance with Islamic law regarding the laws of zakat and the purpose of zakat itself. Praktik pengelolaan distribusi zakat oleh masyarakat Nagari X untuk menciptakan silaturrahmi agar lebih akrab dengan sesame saudara. Malin sebagai orang siak membagi-bagikan zakat secara merata kepada semua yang hadir dalam tasyakuran di rumah muzakki., Namun distribusi tersebut tergolong fakir, miskin dan orang berkemampuan.  Tujuan penelitian ini menjelaskan pelaksanaan zakat pertanian oleh Malin dengan membagikan semua yang diundang oleh muzakki. Dan menjelaskan keabsahan hukum zakat didistribusikan kepada kerabat dengan alasan silaturrahmi sebagai pendekatan penerima zakat. Metode penelitian deskriptif kualitatif dengan pendekatan fenomenologi di Nagari X. Teknik pengambilan data dengan wawancara mendalam kepada masyarakat dan orang siak (malin) secara snowball sampling.. Analisis dilakukan secara  deskriptif kualitatif. Temuan penelitian menyatakan Malin menyerahkan zakat kepada orang-orang yang hadir di acara pertemuan momen penyerahan zakat.  Zakat dibagi berdasarkan jumlah orang yang hadir di pertemuan tersebut. Nominal zakat  sekedar untuk belanja hal hal ringan di bawah Rp.50.00. pada data lapangan. Kesimpulan penelitian ini menunjukkan data penyerahan zakat berdasarkan momen ajang silaturrahmi antara masyarakatnya untuk menjalin persaudaraan semakin erat, sekalipun kaya,  namun hal ini tidak sesuai dengan hasnaf delapan penerima zakat yang fakir miskin, sekalipun terdapat kerabat yang miskin lebih diutamakan. Di samping pihak penerima mesti dari golongan sanaf delapan  dan juga mesti mengangkat taraf ekonominya, bukan sebatas belanja sesaat. Hal ini  tidak membawa arti dalam perubahan ekonominya sesuai  menjadikan penerima zakat untuk kesejahteraan dan meningkat perekonomianya.